Actual Purchase on TikTok Live Streaming Commerce: An Analysis of Utilitarian Shopping Value and Attitude Toward Electronic Live Streaming - Pradnyamitha, Desak Putu; Maradona, Agus Fredy (International Journal of Science and Society, 2024)
This study examines the factors influencing purchasing decisions through TikTok Shop, focusing on live streaming as a promotional medium. In the context of local MSMEs in Indonesia competing with imported products, this research tests the effects of live streaming viewing frequency, parasocial relationships, and social interactivity on purchasing decisions, as well as the mediating roles of utilitarian shopping value and consumer attitudes toward ELS. The research method involves surveys and SEM-PLS analysis with 105 sample. The results show that live streaming viewing frequency does not affect actual purchase, while parasocial relationships and utilitarian value have a positive effect. Consumer attitudes toward ELS also positively influence purchasing decisions. Utilitarian shopping value mediates the effect of live streaming viewing frequency, while consumer attitudes mediate the effect of parasocial relationships. The novelty of this research lies in analyzing the factors influencing purchasing decisions through TikTok and its contribution in providing insights for local MSMEs to design more effective marketing strategies in the digital era.